The Transformation of Economic Life under the Roman Empire Proceedings of the Second Workshop of the International Network Impact of Empire (Roman Empire, c. 200 B.C. - A.D. 476), Nottingham, July 4-7, 2001 - de Blois, L.; Rich, J. (Impact of Empire, 2002)
Ancient history: to c 500 CE